2024
DOI: 10.1002/agt2.475
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated delayed fluorescence Au‐Ag‐oxo nanoclusters: From photoluminescence to radioluminescence

Peng Yuan,
Hansong Zhang,
Yang Zhou
et al.

Abstract: Thermally activated delayed fluorescence (TADF) materials have numerous applications in energy conversion and luminescent imaging. However, they are typically achieved as metal‐organic complexes or pure organic molecules. Herein, we report the largest Au‐Ag‐oxo nanoclusters to date, Au18Ag26(R1COO)12(R2C≡C)24(μ4‐O)2(μ3‐O)2 (Au18Ag26, where R1 = CH3‐, Ph‐, CHOPh‐ or CF3Ph‐; R2 = Ph‐ or FPh‐). These nanoclusters exhibit exceptional TADF properties, including a small S1‐T1 energy gap of 55.5 meV, a high absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…1–6 With the advancement of sophisticated characterization techniques, numerous metal clusters with atomic-level resolved structures have been reported to date. 7–21 It has been observed that the metal core of many of these clusters shares the same polyhedral units, despite variations in peripheral ligands or metal–ligand motif structures. These polyhedral units encompass an M 13 centered icosahedron, 22–28 an M 6 octahedron, 29–35 an M 13 cuboctahedron 36 and an M 7 decahedron, 37–42 among others, where ‘M’ represents Au, Ag, Cu, or other metal atoms or their mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…1–6 With the advancement of sophisticated characterization techniques, numerous metal clusters with atomic-level resolved structures have been reported to date. 7–21 It has been observed that the metal core of many of these clusters shares the same polyhedral units, despite variations in peripheral ligands or metal–ligand motif structures. These polyhedral units encompass an M 13 centered icosahedron, 22–28 an M 6 octahedron, 29–35 an M 13 cuboctahedron 36 and an M 7 decahedron, 37–42 among others, where ‘M’ represents Au, Ag, Cu, or other metal atoms or their mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent metal clusters have attracted significant interest because of their application in the fields of lighting and sensing, etc. 1–4 However, it is challenging to obtain a high emission efficiency and designable wavelength because metal cluster-based emitters have complex energy level structures and excited state relaxation processes. 5,6 Therefore, the building of the relationship between the structure and optical properties is fundamentally important for designing and synthesizing high luminous performance metal clusters.…”
mentioning
confidence: 99%